The Cost of Road Infrastructure in Low and Middle Income Countries - Collier, Paul (World Bank E-Library Archive, 2015)
The connections between transport infrastructure and economic development have been extensively analyzed in previous research, but little is known about the cost of infrastructure investments in poor countries. This paper examines drivers of unit costs of construction and maintenance of transport infrastructure in low and middle income countries and documents that: (i) there is a large dispersion in unit costs for comparable road work activities; (ii) after accounting for environmental drivers of costs, residual unit costs are significantly higher in conflict countries; (iii) there is evidence that costs are higher in countries with higher levels of corruption; (iv) these effects are robust to controlling for a country's public investment capacity and business environment. Our findings have implications for governments aiming to increase connectivity in poor countries